Efektivitas jump shoot tanpa awalan dan jump shoot dengan awalan terhadap hasil tembak jump shoot - Rina Nopiana; Hariadi Hariadi; Lalu Aji Kurniawan; Yuda Atma Wijaya; Abdurrahim Abdurrahim; Adlina Safitri; Alifian Ghazi Asshhidiq; Baiq Melisa Dewi Galuh Kerdap; Fania Sefila Gading; Gilang Pinandika Saputra; Hamzah Amrullah; Lalu Muhammad Suryadi Akbar (Jurnal Porkes, 2024)
This study aims to examine the effectiveness of jump shoot without a prefix and jump shoot with a prefix on the results of jump shoot shooting on basketball teams. This research is an experimental research with randomized pre and test control group design. The population of this study was the basketball team of SMAN 2 Selong 20 people. Sample aggota basketball extracurricular team members SMAN 2 Selong. The sampling technique used saturated sampling technique. Data collection techniques using tests. Data analysis techniques using t test before and after. The results of the data pretets jump shoot without a prefix obtained t count 28.401 and t table 2.093 while the posttest obtained t count 30.431 and t table 2.093. The significant value is 0.00 <0.05, so Ho is rejected Ha is accepted. The pretest jump shoot data results with a prefix obtained t count 23.292 and t table 2.093 while the posttest obtained t count 36.622 and t table 2.093, with a significant value of 0.00 <0.05, Ho is rejected and Ha is accepted. It is concluded that both treatment groups have the effect of training in increasing the shooting accuracy of jump shoot training with a prefix to increase the accuracy of jump shoot shots, accepted. Hypothesis two jump shoot training without a prefix increases the accuracy of jump shoot shots is also answered, accepted